Fatal air embolism caused by air entry into the cardiopulmonary bypass circuit during minimally invasive atrial septal defect repair: a case report - Zeng, Jin; Yang, Yuanyuan; Xiao, Jing (Frontiers in Cardiovascular Medicine, 2025)
An 18-year-old female patient was preoperatively diagnosed with atrial septal defect (ASD) and tricuspid regurgitation. The patient's had a complex secundum-type superior sinus venosus ASD, rather than a primum ASD, which was anatomically unsuitable for transcatheter closure. The patient underwent minimally invasive ASD repair under general anesthesia using three-port totally thoracoscopy with cardiopulmonary bypass (CPB). During the initiation of CPB, poor venous drainage through the right internal jugular vein cannula allowed air to enter the CPB circuit, leading to intraoperative cardiac arrest. Immediate cardiopulmonary resuscitation, intravenous administration of epinephrine, and other emergency interventions were carried out. The procedure was urgently converted to conventional median sternotomy, in order to reestablish CPB and complete the ASD repair. After the operation, the patient developed extensive cerebral air embolism, cerebral edema, brain herniation, and multiorgan failure, including respiratory and circulatory collapse, ultimately resulting in death. This case report analyzes the possible causes of air entry into the CPB system, cerebral air embolism, and the patient's death, aiming to draw lessons to prevent similar serious adverse events, and improve the safety of cardiovascular surgeries.